Innovative Approaches in Multicultural Education-Based Learning in the Social Development of Early Childhood at Raudhatul Athfal Nurul Islam Kindergarten Singkawang City - Hadisa Putri (Journal of Childhood Development, 2024)
Multicultural learning is one of the strategic approaches in supporting early childhood social development, especially in an environment rich in cultural diversity such as in RA Nurul Islam Singkawang. The need to integrate multicultural values in learning in early childhood education institutions is relevant because of the importance of building empathy, tolerance, and social skills from an early age. However, in-depth studies related to the application of innovative approaches based on multicultural education to the development of social attitudes and behavior of early childhood are still limited. This research uses a qualitative method with a case study approach, involving teachers and principals as the main data sources, to identify the effect of the multicultural approach at RA Nurul Islam Singkawang. The results showed that this approach improved children's empathy and tolerance, encouraged more inclusive social interactions, and increased confidence in cross-cultural interactions. In addition, children also showed initiative in conflict resolution and mastery of social skills, such as understanding different perspectives and establishing harmonious relationships. The implications of this study emphasize the importance of integrating multicultural values in the early childhood education curriculum to support better character building and social skills.